The properties of a micro-reactor for the study of the unimolecular decomposition of large molecules - Guan, Qi; Urness, Kimberly N.; Ormond, Thomas K.; David, Donald E.; Barney Ellison, G.; Daily, John W. (International reviews in physical chemistry, 2014)
A micro-reactor system (approximately 0.5-1 mm inner diameter by 2-3 cm in length) coupled with photoionization mass spectrometry and matrix isolation/infrared spectroscopy diagnostics is described. Short residence time flow reactors (roughly ≤ 100 μs) combined with suitable diagnostic tools have the potential to allow observation of unimolecular decomposition processes with minimum interference from secondary reactions. However, achieving the short residence times desired requires very small micro-reactors that are difficult to characterise experimentally because of their size. In this article the benefits of using these micro-reactors are presented along with some details of the systems employed. This is followed by some general flow considerations and then some simple analyses to illustrate particular features of the flow. Finally, computational fluid dynamics simulations are used to explore the flow and chemical behaviour of the reactors in detail. Some findings include: (1) The reactor operates in the laminar domain. (2) Heating and large pressure differences across the reactor result in a compressible flow that chokes (meaning the velocity reaches the sonic condition) at the reactor exit. (3) When helium is the carrier gas, under some circumstances there is slip at the boundaries near the downstream end of the reactor that reduces the pressure drop and heat transfer rate; this effect must be accounted for in the simulations. (4) Because the initial reactant concentration is held to less than 0.1%, secondary reactions are minimised. (5) Although the fluid dynamical residence time from entrance to exit ranges from 25 to 150 μs, in practice the period over which reactions take place is much shorter. In essence, there is a 'sweet spot' within the reactor where most reactions take place. In summary, the micro-reactor, which has been used for many years to generate radicals or study unimolecular decomposition chemical mechanisms, can be used to extract kinetic information by comparing simulations and measurements of reactant and product concentrations at the reactor exit.